2018
DOI: 10.1111/trf.14831
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic thrombocytopenic purpura relapse induced by acute hepatitis E transmitted by cryosupernatant plasma and successfully controlled with ribavirin

Abstract: BACKGROUND Hepatitis E virus (HEV) can be transmitted by transfusion of any type of blood component, but there are few data on the potential risk of transmitting this virus and the associated complications. We provide evidence that HEV can be transmitted by cryosupernatant plasma, and that HEV infection can act as a trigger for thrombotic thrombocytopenic purpura (TTP). STUDY DESIGN AND METHODS A patient with a history of TTP treated with plasmapheresis 2 months previously developed jaundice and a TTP exacerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Transfusion of blood products (red blood cells) containing HEV RNA can cause acute hepatitis E in an immunocompetent patients as recently reported [19]. Interestingly, Riveiro-Barciela et al recently reported a case of HEV associated exacerbation of thrombotic thrombocytopenic purpura transmitted by cryosupernatant plasma [20].…”
Section: Introductionmentioning
confidence: 98%
“…Transfusion of blood products (red blood cells) containing HEV RNA can cause acute hepatitis E in an immunocompetent patients as recently reported [19]. Interestingly, Riveiro-Barciela et al recently reported a case of HEV associated exacerbation of thrombotic thrombocytopenic purpura transmitted by cryosupernatant plasma [20].…”
Section: Introductionmentioning
confidence: 98%
“…HEV infection treated with ribavirin and thrombotic thrombocytopenic purpura remitted with remission of HEV infection. 74…”
Section: Thrombocytopeniamentioning
confidence: 99%
“…People at risk are not only immunosuppressed patients such as transplant recipients or patients with HIV infection but also include cancer patients under chemotherapy or patients with rheumatic diseases. (ii) Clinical effects of an HEV infections had also been observed in immunocompetent individuals with different underlying diseases such as thrombotic thrombocytopenic purpura [59] or systemic lupus erythematosus [60]. (iii) The handling of two different types of donations may be difficult and expensive, and (iv) It is nearly impossible for a physician to assign a patient to an HEV risk in event of an emergency that requires blood transfusion [58].…”
Section: Measures To Prevent Hev Transmissionmentioning
confidence: 99%